Polyarylene sulfide resin composition
By adding a fibrous inorganic filler with a high diameter ratio and an alkoxysilane compound to the polyarylene sulfide resin, the problem of insufficient bending strength and impact strength of the polyarylene sulfide resin molded products is solved, and the production of high-performance molded products is achieved.
Patent Information
- Application Number
- CN202380062179.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-01
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-08
AI Technical Summary
The existing polyarylene sulfide resin molded products have insufficient bending strength and impact strength, making it difficult to meet certain high-performance needs.
A composition containing a polyaryl sulfide resin, a fibrous inorganic filler having a diameter ratio of 3.0 or more, and an alkoxysilane compound is used. Among them, the cooling crystallization temperature of the polyarylene sulfide resin is set to 215° C. or more, the content of the fibrous inorganic filler is between 55 and 180 parts by mass, and the content of the alkoxysilane compound is between 0.5 and 10 parts by mass.
The bending and impact strength of the molded product is significantly improved, making its performance close to or exceed that of traditional high-performance materials.
Smart Images

Figure BDA0005286794860000161
Abstract
Description
Technical Field
[0001] The present invention relates to a polyarylene sulfide resin composition. Background Art
[0002] Polyarylene sulfide resins represented by polyphenylene sulfide resins are widely used in electrical and electronic equipment component materials, automobile component materials, chemical equipment component materials, etc. because of their excellent heat resistance, mechanical properties, chemical resistance, dimensional stability, and flame retardancy.
[0003] In order to improve the mechanical strength of polyarylene sulfide resin molded products, the following technologies have been studied: a technique of adding glass fibers having a flat cross-sectional shape (eg, Patent Document 1); a technique of adding a filler surface-treated with an alkoxysilane compound (eg, Patent Document 2); and the like.
[0004] Patent Document 1: International Publication No. 2021 / 157162
[0005] Patent Document 2: Japanese Patent Application Laid-Open No. 08-012886 Summary of the invention
[0006] An object of the present invention is to provide a polyarylene sulfide resin composition capable of providing a molded article having excellent flexural strength and impact strength.
[0007] The present invention has the following aspects.
[0008] [1] A polyarylene sulfide resin composition comprising:
[0009] (A) polyarylene sulfide resin;
[0010] (B) a fibrous inorganic filler having a ratio of the major axis to the minor axis of a cross section perpendicular to the longitudinal direction, i.e., a different diameter ratio of 3.0 or more; and,
[0011] (C) an alkoxysilane compound,
[0012] The cooling crystallization temperature (Tc) of the polyarylene sulfide resin (A) is 215° C. or higher, wherein the cooling crystallization temperature (Tc) is an exothermic peak temperature accompanied by crystallization observed when the polyarylene sulfide resin (A) is heated to 340° C. and melted and then cooled at a rate of 10° C. / min using a differential scanning calorimeter.
[0013] The content of the fibrous inorganic filler (B) having a ratio of the major axis to the minor axis of a cross section perpendicular to the longitudinal direction, i.e., a different diameter ratio of 3.0 or more, is 55 to 180 parts by mass based on 100 parts by mass of the polyarylene sulfide resin (A).
[0014] The content of the (C) alkoxysilane compound is 0.5 to 10 parts by mass based on 100 parts by mass of the (A) polyarylene sulfide resin.
[0015] [2] The polyarylene sulfide resin composition according to [1], wherein the (C) alkoxysilane compound comprises one or more alkoxysilane compounds having one or more selected from the group consisting of an epoxy group, an amino group, a vinyl group, a (meth)acryloyl group, an isocyanate group and a mercapto group.
[0016] [3] The polyarylene sulfide resin composition according to [1] or [2], wherein the fibrous inorganic filler (B) having a ratio of a major axis to a minor axis in a cross section perpendicular to the longitudinal direction, i.e., a different diameter ratio of 3.0 or more, comprises glass fibers.
[0017] According to the present invention, there can be provided a polyarylene sulfide resin composition capable of providing a molded article having excellent flexural strength and impact strength. DETAILED DESCRIPTION
[0018] Hereinafter, one embodiment of the present invention is described in detail, but the scope of the present invention is not limited to the one embodiment described herein, and various changes can be made without departing from the gist of the present invention. In addition, for a specific parameter, when multiple upper limits and lower limits are recorded, any upper limit and lower limit of these upper limits and lower limits can be combined to form a suitable numerical range. The expression of "X to Y" indicating a numerical range means "above X and below Y". When a specific description recorded in one embodiment is applicable to other embodiments, the description is sometimes omitted in other embodiments.
[0019] [Polyarylene sulfide resin composition]
[0020] The polyarylene sulfide resin composition of the present embodiment (hereinafter, also referred to as "resin composition") comprises: (A) a polyarylene sulfide resin; (B) a fibrous inorganic filler having a ratio of a major axis to a minor axis of a cross section perpendicular to the longitudinal direction, i.e., a different diameter ratio of 3.0 or more; and (C) an alkoxysilane compound, wherein the polyarylene sulfide resin (A) has a cooling crystallization temperature (Tc) of 215°C or more, wherein the cooling crystallization temperature (Tc) is a temperature of 215°C or more obtained by measuring the cooling crystallization temperature of the polyarylene sulfide resin (A) using a differential scanning calorimeter. The ether resin is heated to 340°C and melted, and then cooled at a rate of 10°C / min to form an exothermic peak temperature accompanied by crystallization, the content of the fibrous inorganic filler (B) having a ratio of the major axis to the minor axis of a cross section perpendicular to the longitudinal direction, i.e., a different diameter ratio of 3.0 or more, is 55 to 180 parts by mass relative to 100 parts by mass of the polyarylene sulfide resin (A), and the content of the alkoxysilane compound (C) is 0.5 to 10 parts by mass relative to 100 parts by mass of the polyarylene sulfide resin (A). According to the resin composition of this embodiment, a molded article having excellent flexural strength and impact strength can be provided.
[0021] <(A) Polyarylene sulfide resin>
[0022] (A) The polyarylene sulfide resin is a resin having a repeating unit represented by the following general formula (I).
[0023] -(Ar-S)-···(I)
[0024] (wherein Ar represents an arylene group.)
[0025] The arylene group is not particularly limited, and examples thereof include p-phenylene, m-phenylene, o-phenylene, substituted phenylene, p,p'-diphenylene sulfone, p,p'-biphenylene, p,p'-diphenylene ether, p,p'-diphenylene carbonyl, naphthylene, etc. (A) The polyarylene sulfide resin may be a homopolymer using the same repeating unit as the repeating unit represented by the general formula (I) above, or a copolymer containing different types of repeating units depending on the application.
[0026] As the homopolymer, a homopolymer having a p-phenylene group as an arylene group and a p-phenylene sulfide group as a repeating unit is preferred. This is because a homopolymer having a p-phenylene sulfide group as a repeating unit has extremely high heat resistance, and exhibits high strength, high rigidity, and further high dimensional stability in a wide temperature range. By using such a homopolymer, a molded article having extremely excellent physical properties can be obtained.
[0027] As the copolymer, a combination of two or more different aryl sulfide groups among the arylene groups can be used. Among these, from the viewpoint of obtaining a molded product having high physical properties such as heat resistance, moldability, and mechanical properties, a combination containing a p-phenylene sulfide group and a m-phenylene sulfide group is preferred. A polymer containing 70 mol% or more of a p-phenylene sulfide group is more preferred, and a polymer containing 80 mol% or more of a p-phenylene sulfide group is further preferred. It should be noted that the (A) polyarylene sulfide resin having a phenylene sulfide group is a polyphenylene sulfide resin (PPS resin).
[0028] Generally, polyarylene sulfide resins are known to have a molecular structure that is substantially linear and has no branching or crosslinking structure, and a molecular structure that has branching or crosslinking structure, depending on the production method. However, any type of these can be used as the (A) polyarylene sulfide resin.
[0029] From the viewpoint of improving molding processability and toughness, (A) polyarylene sulfide resin was heated at 310°C and a shear rate of 1200 sec. -1 The measured melt viscosity is preferably 3 to 250 Pa·s, more preferably 5 to 150 Pa·s, and even more preferably 8 to 80 Pa·s.
[0030] The cooling crystallization temperature (Tc) of the polyarylene sulfide resin (A) is 215° C. or higher, preferably higher than 215° C., more preferably 216° C. or higher, further preferably 220° C. or higher, and particularly preferably 230° C. or higher. When the cooling crystallization temperature (Tc) of the polyarylene sulfide resin (A) is 215° C. or higher, surprisingly, the synergistic effect of the combined use with the alkoxysilane compound (C) described later can be fully obtained, and the flexural strength and impact strength of the molded article can be improved.
[0031] The upper limit of the cooling crystallization temperature (Tc) of the polyarylene sulfide resin (A) is preferably 260° C. or lower, more preferably 250° C. or lower, particularly preferably 240° C. or lower.
[0032] In one embodiment, the cooling crystallization temperature (Tc) of the polyarylene sulfide resin (A) may be 215 to 260° C., may be more than 215° C. and 260° C., may be 216 to 250° C., or may be 216 to 240° C. In one embodiment, the cooling crystallization temperature (Tc) of the polyarylene sulfide resin (A) may be 219° C., or may be a range in which this is the upper limit or lower limit of the above numerical range.
[0033] The cooling crystallization temperature (Tc) is the exothermic peak temperature accompanying crystallization observed when the (A) polyarylene sulfide resin is heated to 340°C and melted by a differential scanning calorimeter and then cooled at a rate of 10°C / min.
[0034] As a method for adjusting the cooling crystallization temperature (Tc) of the (A) polyarylene sulfide resin to 215°C or above, a method based on a washing treatment after polymerization is simple in terms of process and is preferred, but is not necessarily limited to this method. As a method based on a washing treatment, for example, a method of washing the polymer after polymerization with an acidic aqueous solution of appropriate acidity can be cited. In this case, as an acid used as an acidic aqueous solution, inorganic acids such as hydrochloric acid, sulfuric acid, and ammonium chloride can be cited; saturated fatty acids such as acetic acid, formic acid, propionic acid, butyric acid, valeric acid, and caproic acid; unsaturated fatty acids such as acrylic acid, crotonic acid, and oleic acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, and salicylic acid; dicarboxylic acids such as oxalic acid, maleic acid, and fumaric acid; methanesulfonic acid, p-toluenesulfonic acid, etc., among which hydrochloric acid, acetic acid, and ammonium chloride are preferred. In addition, before and after washing based on the acidic aqueous solution, washing can be performed with an organic solvent such as acetone or water as needed. For example, when the cooling crystallization temperature (Tc) is low, the cooling crystallization temperature (Tc) of the polyarylene sulfide resin (A) can be increased to 215° C. or higher by washing the polyarylene sulfide resin (A) with the above-mentioned compound (e.g., acetic acid, ammonium chloride, etc.).
[0035] (A) The method for producing the polyarylene sulfide resin is not particularly limited, and the polyarylene sulfide resin can be produced by a conventionally known production method. For example, after synthesizing a low molecular weight polyarylene sulfide resin, it is polymerized in the presence of a known polymerization aid at a high temperature to obtain a high molecular weight, thereby producing the polyarylene sulfide resin. In addition, it can also be produced by blending a plurality of polyarylene sulfide resins. In this case, it is also possible to combine the polyarylene sulfide resins with different melt viscosities to produce the polyarylene sulfide resin. When combining polyarylene sulfide resins with different melt viscosities, it is preferred that the melt viscosity of the obtained resin is within the above range. In addition, the cooling crystallization temperature (Tc) of the obtained resin is within the range of 215°C or more, and two or more polyarylene sulfide resins with different cooling crystallization temperatures (Tc) can also be combined and used.
[0036] The polyarylene sulfide resin produced by a general polymerization method is usually washed several times with water or an organic solvent such as acetone to remove by-product impurities, etc. As described above, in one embodiment, the (A) polyarylene sulfide resin may be further washed with acetic acid, ammonium chloride, etc.
[0037] In one embodiment, the content of the polyarylene sulfide resin (A) in the resin composition is preferably 30% by mass or more, more preferably 35% by mass or more. In one embodiment, the content of the polyarylene sulfide resin (A) in the resin composition may be 30 to 70% by mass, 30 to 65% by mass, or 35 to 60% by mass.
[0038] In one embodiment, the thermoplastic resin contained in the resin composition may be preferably 80% by mass or more, more preferably 90% by mass or more, of the thermoplastic resin contained in the resin composition may be (A) polyarylene sulfide resin. In one embodiment, the thermoplastic resin contained in the resin composition may be composed only of (A) polyarylene sulfide resin.
[0039] <(B) Fibrous inorganic filler>
[0040] The resin composition contains: a fibrous inorganic filler (hereinafter also referred to as "(B) fibrous inorganic filler") having a ratio of the major axis to the minor axis of a cross section perpendicular to the longitudinal direction (major axis of the cross section / minor axis of the cross section), i.e., a diameter ratio (hereinafter also referred to as "diameter ratio") of 3.0 or more.
[0041] The "long diameter of the cross section at right angles to the length direction" is the longest straight-line distance in the cross section at right angles to the length direction of the fiber, and the "short diameter of the cross section at right angles to the length direction" is the longest straight-line distance at right angles to the long diameter in the cross section. The diameter ratio refers to the diameter ratio of the initial shape (shape before melt kneading). The diameter ratio can be calculated using a scanning electron microscope and image processing software, and is recorded as the arithmetic mean value measured for 10 (B) fibrous inorganic fillers. The diameter ratio can also use the manufacturer's value (the value published by the manufacturer in the catalog, etc.).
[0042] Generally, as indicators of the mechanical strength of a resin molded product, there are: tensile strength showing the strength when a tensile force is applied to the molded product, flexural strength showing the strength when a bending load is applied to the molded product, and impact strength showing the strength when an impact is applied to the molded product, etc. The directions of force application and the methods of applying force of these indicators are different, so there is no relationship that if one indicator is excellent, the other indicators are also excellent. For example, even if the tensile strength is excellent, the flexural strength may not be excellent. The resin composition of this embodiment can provide a molded product with excellent mechanical strength, especially flexural strength and impact strength, by using a specified amount of (B) a fibrous inorganic filler having a specified diameter ratio and (C) an alkoxysilane compound described later in (A) a polyarylene sulfide resin.
[0043] The diameter ratio of the fibrous inorganic filler (B) is 3.0 or more, preferably 3.5 or more, and more preferably 3.8 or more. The upper limit of the diameter ratio is 10.0 or less, preferably 8.0 or less, and more preferably 6.0 or less. In one embodiment, the diameter ratio of the fibrous inorganic filler (B) can be 3.0 to 10.0, 3.5 to 8.0, or 3.8 to 6.0. In one embodiment, the diameter ratio of the fibrous inorganic filler (B) can be 4.0, which can be a range that uses it as the upper limit or lower limit of the above numerical range.
[0044] Examples of the (B) fibrous inorganic filler include fibrous inorganic fillers having a cross-sectional shape perpendicular to the longitudinal direction of the fiber of an ellipse, a semicircle, a cocoon shape (a shape in which a portion of the longitudinal direction of the ellipse is recessed inward), a rectangle, or similar shapes thereof.
[0045] The major axis of the cross section perpendicular to the longitudinal direction of the fibrous inorganic filler (B) is preferably 10 to 40 μm, more preferably 20 to 30 μm.
[0046] The minor axis of the cross section perpendicular to the longitudinal direction of the fibrous inorganic filler (B) is preferably 1 to 20 μm, more preferably 3 to 10 μm.
[0047] The major and minor axes of the cross section at right angles to the longitudinal direction can be calculated using a scanning electron microscope and image processing software, and recorded as the arithmetic mean value measured for 10 (B) fibrous inorganic fillers. In addition, the major and minor axes of the cross section at right angles to the longitudinal direction can also be manufacturer values (values published by the manufacturer in the catalog, etc.).
[0048] For the average fiber length of (B) fibrous inorganic filler, from the viewpoint of further improving the bending strength and impact strength of the molded product, the average fiber length (cut length) before melt kneading in the resin composition is preferably 0.01 to 3.5 mm, more preferably 0.05 to 3.5 mm, further preferably 0.1 to 3.5 mm, and particularly preferably 0.5 to 3 mm. The average fiber length can be calculated using a scanning electron microscope and image processing software, and is recorded as the arithmetic mean value measured for 1000 (B) fibrous inorganic fillers. The average fiber length can also be a manufacturer's value (the value published by the manufacturer in the catalog, etc.).
[0049] The average fiber length of the (B) fibrous inorganic filler in the molded article is preferably 50 to 1000 μm, more preferably 100 to 900 μm, from the viewpoint of further improving the bending strength and impact strength of the molded article. The average fiber length of the (B) fibrous inorganic filler in the molded article can be calculated as follows: the molded article is heated at 600° C. for 3 to 5 hours and ashed to obtain a residue, 3 mg of the obtained residue is dispersed in a 5% polyethylene glycol aqueous solution, and after sufficient stirring, 10 mL is transferred to a culture dish, and calculated using an image measuring machine, and recorded as the arithmetic mean value measured for 1000 (B) fibrous inorganic fillers.
[0050] In terms of ease of production, the cross-sectional area of the fibrous inorganic filler (B) is preferably 1×10 -5 ~1×10 -3 mm 2 , more preferably 1×10 -4 ~5×10 -4mm 2 The "cross-sectional area" can be recorded as a value obtained by multiplying the value obtained by dividing the major axis by 2 and the value obtained by dividing the minor axis by 2, with the longest straight-line distance of the cross section of the (B) fibrous inorganic filler measured using a scanning electron microscope and image processing software as the major axis and the shortest straight-line distance as the minor axis, and further multiplying the obtained value by pi. The cross-sectional area is recorded as the arithmetic mean value measured for 10 (B) fibrous inorganic fillers.
[0051] As the material of (B) fibrous inorganic filler, mineral fibers such as glass fiber, carbon fiber, zinc oxide fiber, titanium oxide fiber, wollastonite, silica fiber, silica-alumina fiber, zirconium oxide fiber, boron nitride fiber, silicon nitride fiber, boron fiber, potassium titanate fiber, stainless steel fiber, aluminum fiber, titanium fiber, copper fiber, brass fiber, etc. can be cited, preferably using one or more of these selected from. Among them, more preferably including glass fiber. In addition, for the purpose of reducing the specific gravity of the resin combination, hollow fibers can also be used as (B) fibrous inorganic filler.
[0052] The (B) fibrous inorganic filler can be surface treated with various surface treatment agents such as commonly known epoxy compounds, isocyanate compounds, silane compounds, titanate compounds, fatty acids, etc. The surface treatment can improve the adhesion with the (A) polyarylene sulfide resin. The surface treatment agent can be used in advance for the (B) fibrous inorganic filler to perform surface treatment or clustering treatment before preparing the material, or can be added simultaneously when preparing the material.
[0053] The content of the fibrous inorganic filler (B) is 55 to 180 parts by mass, preferably 58 to 170 parts by mass, more preferably 60 to 160 parts by mass, and further preferably 65 to 155 parts by mass, relative to 100 parts by mass of the polyarylene sulfide-based resin (A). When the content of the fibrous inorganic filler (B) is 55 to 180 parts by mass relative to 100 parts by mass of the polyarylene sulfide-based resin (A), a synergistic effect due to the combined use with the alkoxysilane compound (C) described later can be sufficiently obtained, and the flexural strength and impact strength of the molded article can be improved.
[0054] In one embodiment, the content of the fibrous inorganic filler (B) may be 68 to 153 parts by mass relative to 100 parts by mass of the polyarylene sulfide-based resin (A). In one embodiment, the content of the fibrous inorganic filler (B) may be 68 parts by mass, 101 parts by mass, 102 parts by mass, 153 parts by mass, or a range in which these are upper or lower limits, relative to 100 parts by mass of the polyarylene sulfide-based resin (A).
[0055] The content of the fibrous inorganic filler (B) in the resin composition is preferably 35 to 65% by mass, more preferably 36 to 64% by mass. In one embodiment, the content of the fibrous inorganic filler (B) in the resin composition may be 40 to 61% by mass.
[0056] The resin composition may contain other inorganic fillers other than the fibrous inorganic filler (B) as required as described later, but the content of the fibrous inorganic filler (B) in the total inorganic filler is preferably 50% by mass or more, more preferably 80% by mass or more, and further preferably 90% by mass or more. In one embodiment, the inorganic filler may also be formed by the fibrous inorganic filler (B).
[0057] <Other inorganic fillers>
[0058] The resin composition may contain other inorganic fillers in addition to the (B) fibrous inorganic filler as needed. Examples of the other inorganic filler include fibrous inorganic fillers other than the (B) fibrous inorganic filler and non-fibrous inorganic fillers.
[0059] As fibrous inorganic fillers other than (B) fibrous inorganic fillers, fibrous fillers having a ratio of the major diameter to the minor diameter of a cross section at right angles to the length direction, i.e., a different diameter ratio, of less than 3.0, less than 2.0, or less than 1.5 can be cited. As fibrous inorganic fillers other than (B) fibrous inorganic fillers, for example, fibrous inorganic fillers having a circular or square cross-sectional shape at right angles to the length direction of the fiber can be cited. The material of fibrous inorganic fillers other than (B) fibrous inorganic fillers is not limited, and the fibrous fillers exemplified in the above-mentioned (B) fibrous inorganic fillers can be cited, and can include one or more selected from these. The material of the fibrous inorganic filler (B) and the fibrous inorganic fillers other than (B) fibrous inorganic fillers can be the same or different. The average fiber length and average fiber diameter of other fibrous inorganic fillers are not limited.
[0060] Examples of the non-fibrous inorganic filler include a powdery inorganic filler and a plate-like inorganic filler.
[0061] As the granular inorganic filler, carbon black, silicon dioxide, quartz powder, glass beads, glass powder, talc (granular), silicates such as calcium silicate, aluminum silicate, diatomaceous earth, metal oxides such as iron oxide, titanium oxide, zinc oxide, aluminum oxide, metal carbonates such as calcium carbonate, magnesium carbonate, metal sulfates such as calcium sulfate, barium sulfate, and silicon carbide, silicon nitride, boron nitride, various metal powders, etc. can be cited, and one or more selected from these can be included. As the plate-like inorganic filler, for example, glass flakes, talc (plate-like), mica, kaolin, clay, aluminum oxide, various metal foils, etc. can be cited, and one or more selected from these can be included. The average particle size (D50) of the non-fibrous inorganic filler is not limited, and can be set to 0.1 to 100 μm, for example.
[0062] The content of other inorganic fillers is not limited, and can be, for example, 0 to 50 parts by mass, or less than 40 parts by mass, relative to 100 parts by mass of the (A) polyarylene sulfide resin. In one embodiment, the content of other inorganic fillers is preferably small.
[0063] In one embodiment, the content of the fibrous filler having a ratio of the major diameter to the minor diameter of a cross section perpendicular to the longitudinal direction, i.e., a different diameter ratio, of less than 3.0 is preferably less than 1 part by mass, more preferably less than 0.5 part by mass, and further preferably less than 0.1 part by mass, based on 100 parts by mass of the (A) polyarylene sulfide resin. In one embodiment, the composition may be configured so as not to contain a fibrous filler having a ratio of the major diameter to the minor diameter of a cross section perpendicular to the longitudinal direction, i.e., a different diameter ratio, of less than 3.0.
[0064] <(C) Alkoxysilane compound>
[0065] The resin composition contains (C) an alkoxysilane compound. The (C) alkoxysilane compound preferably contains one or more alkoxysilane compounds having one or more selected from the group consisting of an epoxy group, an amino group, a vinyl group, a (meth)acryloyl group, an isocyanate group, and a mercapto group.
[0066] In one embodiment, the (C) alkoxysilane compound is preferably represented by the following formula (II).
[0067] R 1 n Si(OR 2 ) 4-n (II)
[0068] In formula (II), R 1 is an alkyl group having 1 to 18 (preferably 1 to 10) carbon atoms and having an epoxy group, an amino group, a vinyl group, a (meth)acryloyl group, an isocyanate group or a mercapto group, R 2 It is an alkyl group having 1 to 4 carbon atoms, and n is an integer of 1 to 3.
[0069] As the (C) alkoxysilane compound, for example, epoxyalkoxysilane, aminoalkoxysilane, vinylalkoxysilane, (meth)acryloylalkoxysilane, isocyanatealkoxysilane, mercaptoalkoxysilane and the like alkoxysilanes can be mentioned, and it is preferred to contain one or more of them. It should be noted that the number of carbon atoms of the alkoxy group is preferably 1 to 10, particularly preferably 1 to 4. The (C) alkoxysilane compound may contain one or more of them.
[0070] Examples of the epoxyalkoxysilane include γ-glycidoxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and γ-glycidoxypropyltriethoxysilane.
[0071] As aminoalkoxysilane, for example, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-diallylaminopropyltrimethoxysilane, γ-diallylaminopropyltriethoxysilane and the like can be mentioned.
[0072] Examples of the vinylalkoxysilane include vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltri(β-methoxyethoxy)silane.
[0073] Examples of the (meth)acryloylalkoxysilane include γ-acryloxypropyltriethoxysilane, γ-acryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane and γ-methacryloxypropylmethyldiethoxysilane.
[0074] Examples of the isocyanate alkoxysilane include γ-isocyanate propyl triethoxysilane and γ-isocyanate propyl trimethoxysilane.
[0075] Examples of the mercaptoalkoxysilane include γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane.
[0076] Among these, it is more preferred that at least one selected from epoxyalkoxysilane and aminoalkoxysilane is contained, and it is particularly preferred that γ-aminopropyltriethoxysilane is contained.
[0077] The content of the alkoxysilane compound (C) is 0.5 to 10 parts by mass, preferably 0.6 to 8 parts by mass, and more preferably 0.7 to 4.5 parts by mass, relative to 100 parts by mass of the polyarylene sulfide resin (A). When the content of the alkoxysilane compound (C) is 0.5 to 10 parts by mass relative to 100 parts by mass of the polyarylene sulfide resin (A), a synergistic effect due to the combined use with the fibrous inorganic filler (B) can be sufficiently obtained, and the flexural strength and impact strength of the molded article can be improved.
[0078] In one embodiment, the content of the alkoxysilane compound (C) may be 0.5 parts by mass, 1.0 parts by mass, 1.2 parts by mass, 1.5 parts by mass, or a range with these as upper limits or lower limits, relative to 100 parts by mass of the polyarylene sulfide resin (A).
[0079] As described above, the (B) fibrous inorganic filler can be surface treated with a silane compound or the like. In one embodiment, when the (B) fibrous inorganic filler is surface treated with an alkoxysilane compound, the content of the (C) alkoxysilane compound can include the content of the alkoxysilane compound derived from the surface treatment agent. In this case, it is also preferred that the content of the (C) alkoxysilane compound is within the above range.
[0080] (Other additives, etc.)
[0081] The resin composition can contain known additives added to conventional thermoplastic resins and thermosetting resins according to the desired performance to impart the desired characteristics that meet its purpose within the scope of not hindering the effect of the present invention. As additives, burr inhibitors, mold release agents, lubricants, plasticizers, flame retardants, colorants such as dyes and pigments, crystallization accelerators, crystallization nucleating agents, various antioxidants, heat stabilizers, weathering stabilizers and preservatives can be cited. As mold release agents, polyethylene wax, fatty acid esters, fatty amides, etc. can be cited. As crystallization nucleating agents, boron nitride, talc, kaolin, carbon black, carbon nanotubes, etc. can be cited. As preservatives, zinc oxide, zinc carbonate, etc. can be cited. The content of the above-mentioned additives can be set to less than 5% by mass in the whole resin composition.
[0082] In addition, in the resin composition, in addition to the aforementioned components, a small amount of other thermoplastic resin components can also be used auxiliaryly according to its purpose. As other thermoplastic resins used herein, any one can be used as long as it is a resin that is stable at high temperatures. For example, aromatic polyesters, polyamides, polycarbonates, ABS, polyphenylene sulfide, polyalkyl acrylate, polysulfone, polyether sulfone, polyetherimide, polyether ketone, fluororesin, liquid crystal polymer, cyclic olefin copolymers, etc. formed by aromatic dicarboxylic acids and glycols, or hydroxycarboxylic acids, such as polyethylene terephthalate and polybutylene terephthalate, can be cited. In addition, these thermoplastic resins can also be mixed with more than two and used. The content of other thermoplastic resin components can be set to less than 20% by mass in the whole resin composition, for example.
[0083] (Method for producing polyarylene sulfide resin composition)
[0084] The method for producing the resin composition is not particularly limited, and the resin composition can be produced by melt-kneading the above-mentioned components by a known method. For example, any of the following methods can be used: a method of mixing the components and then kneading and extruding them in an extruder to prepare pellets; a method of temporarily preparing pellets of different compositions, mixing a predetermined amount of the pellets and subjecting them to molding, and obtaining a molded product of a target composition after molding; a method of directly feeding one or more of the components into a molding machine; etc.
[0085] The tensile strength (TS) of the molded article of the resin composition is preferably 195 MPa or more. If it is 195 MPa or more, it can be said that it has a tensile strength equal to or greater than that of the past. According to the resin composition of the present embodiment, a molded article having a tensile strength equal to or greater than that of the past can be provided. The tensile strength (TS) is recorded as the value obtained as follows: After the pellets of the resin composition are dried at 140°C for 3 hours, a type A test piece (width 10 mm, thickness 4 mmt) according to ISO3167:93 is made by injection molding at a barrel temperature of 320°C and a mold temperature of 150°C, and the test piece is used to obtain the value measured according to ISO527-1,2.
[0086] The flexural strength (FS) of the molded article of the resin composition is preferably 290MPa or more, more preferably 300MPa or more. According to the resin composition of the present embodiment, a molded article having improved flexural strength can be provided. The flexural strength (FS) is recorded as the value obtained as follows: after the pellets of the resin composition are dried at 140°C for 3 hours, a test piece (width 10mm, thickness 4mmt) according to ISO316 is made by injection molding at a barrel temperature of 320°C and a mold temperature of 150°C, and the test piece is used to obtain the value measured according to ISO178.
[0087] The Charpy impact strength (notched) of the molded article of the resin composition is preferably 11.0 kJ / m 2 More preferably 11.5 kJ / m 2 More preferably 15.0 kJ / m 2 The above. According to the resin composition of the present embodiment, a molded product having improved Charpy impact strength than before can be provided. The Charpy impact strength is recorded as the value obtained as follows: After the pellets of the resin composition are dried at 140°C for 3 hours, a test piece (width 10 mm, thickness 4 mmt, with notch) according to ISO316 is made by injection molding at a barrel temperature of 320°C and a mold temperature of 150°C, and the test piece is used to measure the value according to ISO179-1.
[0088] (use)
[0089] The resin composition of the present embodiment can provide a molded article having excellent flexural strength and impact strength, and therefore can be used for various applications such as electrical / electronic equipment parts, automobile parts, and chemical equipment parts. Specific embodiments
[0091] Hereinafter, the present invention will be described in more detail with reference to Examples, but the interpretation of the present invention is not limited to these Examples.
[0092] [Examples 1 to 7, Comparative Examples 1 to 11]
[0093] Using the materials shown below, polyarylene sulfide resin, fibrous inorganic filler and alkoxysilane compound were dry-blended in the composition and content ratio shown in Table 1. The mixture was fed into a twin-screw extruder (glass fiber was separately added from the side feed section of the extruder) at a barrel temperature of 320° C. and melt-kneaded to obtain resin composition pellets of Examples and Comparative Examples.
[0094] (Polyarylene sulfide resin)
[0095] PPS-1: polyphenylene sulfide resin, "Fortron KPS" manufactured by KUREHA CORPORATION (melt viscosity: 30 Pa·s (shear rate: 1200 sec -1 , 310℃), Tc: 219℃)
[0096] PPS-2: Polyphenylene sulfide resin (Tc: 183°C) synthesized by the following method
[0097] (Synthesis Method of PPS-2)
[0098] 5700 g of NMP was placed in a 20 L autoclave, and after replacing with nitrogen, the temperature was raised to 100° C. over about 1 hour while stirring with a stirrer at 250 rpm. After reaching 100° C., 1170 g of a 74.7 wt % NaOH aqueous solution, 1990 g of a sulfur source aqueous solution (containing 21.8 mol of NaSH and 0.50 mol of Na2S) and 1000 g of NMP were added, and the temperature was slowly raised to 200° C. over about 2 hours, and 945 g of water, 1590 g of NMP and 0.31 mol of hydrogen sulfide were discharged to the outside of the system.
[0099] After the dehydration step, the mixture was cooled to 170° C., and 3459 g of p-DCB, 2800 g of NMP, 133 g of water, and 23 g of NaOH having a concentration of 97% by weight were added, resulting in a temperature in the kettle of 130° C. Then, the mixture was heated to 180° C. over 30 minutes while stirring at a stirring speed of 250 rpm, and further heated from 180° C. to 220° C. over 60 minutes. After reacting at this temperature for 60 minutes, the mixture was heated to 230° C. over 30 minutes, and reacted at 230° C. for 90 minutes to perform preliminary polymerization.
[0100] After the end of the preliminary polymerization, the speed of the stirrer was immediately increased to 400 rpm, and 340 g of water was pressed in. After the water was pressed in, the temperature was raised to 260°C within 1 hour, and the reaction was carried out at this temperature for 5 hours to carry out the post-polymerization. After the end of the post-polymerization, the reaction mixture was cooled to near room temperature, and the contents were screened out with a 100-mesh wire mesh to obtain a granular polymer. Then, the granular polymer was washed with acetone 3 times and water 5 times to obtain a washed granular polymer. The granular polymer was dried at 105°C for 13 hours. The melt viscosity of the granular polymer obtained in this way (shear rate: 1200sec -1 , 310°C) was 30 Pa·s. This operation was repeated 5 times to obtain the desired amount of polymer (PPS-2).
[0101] (Measurement of melt viscosity of PPS resin)
[0102] The melt viscosity of the PPS resin was measured as follows. A capillary rheometer manufactured by Toyo Seiki Seisaku-sho Co., Ltd. was used. The flat die is used as a capillary, the barrel temperature is 310℃, and the shear rate is 1200sec. -1 The melt viscosity is below.
[0103] (Measurement method of Tc)
[0104] The Tc of the above-mentioned PPS resin is measured as follows.
[0105] About 5 mg of PPS resin was weighed and heated at a rate of 10°C / min using a differential scanning calorimeter DSC-8500 manufactured by PerkinElmer Co., Ltd. The temperature was maintained at 340°C for 5 minutes and then cooled at a rate of 10°C / min. The crystallization peak (exothermic peak) temperature was read from the obtained DSC graph and used as Tc.
[0106] (Fiber-like inorganic filler)
[0107] GF1: Glass fiber, manufactured by Nippon Electric Glass Co., Ltd., flat glass fiber ESC03T-760-FGF, oval cross section, major diameter 28 μm, minor diameter 7 μm, major diameter / minor diameter ratio 4.0, average fiber length 3 mm
[0108] GF2: Glass fiber, manufactured by Nitto Boseki Co., Ltd., special-section chopped fiber CSG 3PA-830, oval cross section, major diameter 28 μm, minor diameter 7 μm, major diameter / minor diameter ratio 4.0, average fiber length 3 mm
[0109] Comparison GF: Glass fiber, manufactured by Nippon Electric Glass Co., Ltd., chopped fiber ECS03T-717, approximately circular cross section, major diameter 13 μm, minor diameter 13 μm, major diameter / minor diameter ratio 1.0, average fiber length 3 mm
[0110] (Alkoxysilane compound)
[0111] Alkoxysilane compound: γ-aminopropyltriethoxysilane, "KBE-903P" manufactured by Shin-Etsu Chemical Co., Ltd.
[0112] [Measurement]
[0113] (Tensile strength: TS)
[0114] After drying the resin composition pellets obtained in the examples and comparative examples at 140°C for 3 hours, the A-type test piece (width 10 mm, thickness 4 mmt) according to ISO3167:93 was made by injection molding at a molding barrel temperature of 320°C and a mold temperature of 150°C. The tensile strength (MPa) was measured using the test piece according to ISO527-1,2. The results are shown in Table 1. When the tensile strength is 195 MPa or more, it is evaluated as having a tensile strength equal to or greater than that of the past.
[0115] (Flexural Strength: FS)
[0116] After the resin composition pellets obtained in the examples and comparative examples were dried at 140°C for 3 hours, test pieces (width 10 mm, thickness 4 mmt) according to ISO316 were prepared by injection molding at a molding barrel temperature of 320°C and a mold temperature of 150°C. The bending strength (MPa) was measured according to ISO178 using the test piece. The results are shown in Table 1. When the bending strength is 290 MPa or more, it is evaluated as excellent in bending strength.
[0117] (Charpy impact strength (notched))
[0118] The resin composition pellets obtained in the examples and comparative examples were dried at 140°C for 3 hours and then injection molded to produce test pieces (10 mm in width and 4 mm in thickness) in accordance with ISO 316 at a molding barrel temperature of 320°C and a mold temperature of 150°C. The Charpy impact strength (notched) (kJ / m 2 ). The results are shown in Table 1. Charpy impact strength is 11.0 kJ / m 2 In the above case, it was evaluated that the impact strength was excellent.
[0119] [Table 1]
[0120]
[0121] As shown in Table 1, the flexural strength of the resin compositions of Examples 1 to 7 were all 290 MPa or more, and the Charpy impact strength was all 11.0 kJ / m 2 As a result, a molded product with excellent bending strength and impact strength can be provided. In addition, the tensile strength is 195 MPa or more, which is equivalent to or higher than that of the conventional molded product.
[0122] On the other hand, the resin compositions of Comparative Examples 1 to 6 used fibrous inorganic fillers having a diameter difference ratio of less than 3.0, and even if they contained alkoxysilane compounds as in Comparative Examples 1 to 3, they could not achieve both excellent flexural strength and impact strength.
[0123] In the resin composition of Comparative Example 7, the content of the alkoxysilane compound was less than 0.5 parts by mass based on 100 parts by mass of the polyarylene sulfide resin, resulting in poor flexural strength.
[0124] In the resin composition of Comparative Example 8, the cooling crystallization temperature (Tc) of the polyarylene sulfide resin was lower than 215° C., resulting in poor flexural strength.
[0125] The resin compositions of Comparative Examples 9 to 11 did not contain an alkoxysilane compound, but had poor bending strength even when a fibrous inorganic filler having a diameter difference ratio of 3.0 or more was used.
[0126] In addition, as shown in Comparative Examples 1, 7, 8, 10, and 11, even when the tensile strength is high exceeding 195 MPa, the effect of improving the bending strength is not obtained.
[0127] Industrial Applicability
[0128] The resin composition of the present embodiment can provide a molded product having excellent flexural strength and impact strength, and therefore can be suitably used for electrical / electronic equipment component materials, automobile component materials, chemical equipment component materials, and the like, and has industrial applicability.
Claims
1. A polyarylene sulfide resin composition, comprising: (A) polyarylene sulfide resin; (B) a fibrous inorganic filler having a ratio of the major axis to the minor axis of a cross section perpendicular to the longitudinal direction, i.e., a different diameter ratio of 3.0 or more; and, (C) an alkoxysilane compound, The cooling crystallization temperature (Tc) of the polyarylene sulfide resin (A) is 215° C. or higher, wherein: The cooling crystallization temperature (Tc) is an exothermic peak temperature accompanied by crystallization observed when the (A) polyarylene sulfide resin is heated to 340°C and melted using a differential scanning calorimeter and then cooled at a rate of 10°C / min. The content of the fibrous inorganic filler (B) having a ratio of the major axis to the minor axis of a cross section perpendicular to the longitudinal direction, i.e., a different diameter ratio of 3.0 or more, is 55 to 180 parts by mass based on 100 parts by mass of the polyarylene sulfide resin (A), The content of the (C) alkoxysilane compound is 0.5 to 10 parts by mass based on 100 parts by mass of the (A) polyarylene sulfide resin.
2. The polyarylene sulfide resin composition according to claim 1, wherein The (C) alkoxysilane compound includes one or more alkoxysilane compounds having one or more selected from the group consisting of an epoxy group, an amino group, a vinyl group, a (meth)acryloyl group, an isocyanate group, and a mercapto group.
3. The polyarylene sulfide resin composition according to claim 1 or 2, wherein The fibrous inorganic filler (B) having a ratio of a major axis to a minor axis in a cross section perpendicular to the longitudinal direction, that is, a diameter difference ratio of 3.0 or more includes glass fibers.
Citation Information
Patent Citations
Polyarylene sulfide resin composition
JP1996012886A
Glass-fiber-reinforced resin composition and molded glass-fiber-reinforced resin article
WO2021157162A1